2024
DOI: 10.1039/d3sm01301d
|View full text |Cite
|
Sign up to set email alerts
|

Supramolecular gels – a panorama of low-molecular-weight gelators from ancient origins to next-generation technologies

David K. Smith

Abstract: Supramolecular gels, self-assembled from low-molecular-weight gelators (LMWGs), have a long history and a bright future.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(14 citation statements)
references
References 598 publications
(529 reference statements)
0
10
0
Order By: Relevance
“…First, NaOD (0.5 M, 40 μL) was added on top of the multicomponent gel to deprotonate Nap-FF. After 72 h, 1 H NMR indicated that approximately 73% of the Nap-FF network had been converted into the mobile solution phase. Conversely, only slight solubilization of DBS-CONHNH 2 (ca.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…First, NaOD (0.5 M, 40 μL) was added on top of the multicomponent gel to deprotonate Nap-FF. After 72 h, 1 H NMR indicated that approximately 73% of the Nap-FF network had been converted into the mobile solution phase. Conversely, only slight solubilization of DBS-CONHNH 2 (ca.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…27 Characterization data were in agreement with previous reports. 1 H NMR spectra were recorded on a Jeol 400 spectrometer ( 1 H 400 MHz). Samples were prepared as solutions in deuterated NMR solvents (DMSO-d 6 or D 2 O), and chemical shifts (δ) are quoted in parts per million (ppm) referenced to residual solvent.…”
Section: ■ Experimental Sectionmentioning
confidence: 99%
“…Furthermore, the nucleophilicity grows going down the periodic table (F − < Cl − < Br − < I − ) for polar protic solvents [43], that is, F − is the softest anion in its interaction with the surface of the CSS nanoparticles. Literature analysis shows [5,31] the various LMWGs undergo only gel-sol transitions under the action of F − . Thereby, we have demonstrated for the first time that fluoride anions can lead to a reversible sol-gel transition, whose peculiarities have been studied in the present paper using modern instrumental techniques.…”
Section: Visual Analysis Of Sol-gel Transition Processmentioning
confidence: 99%
“…Herewith, less attention is paid to low-molecular-weight compounds. The self-assembly process in such systems, for example, in an aqueous medium, leads to the unusual phenomenon of gel formation, which is observed at a low content of the dispersed phase [5]. Such gels are supramolecular objects.…”
Section: Introductionmentioning
confidence: 99%
“…This has prompted researchers to mimic nature's design to develop functional materials by employing the self-assembly of synthetic multi-component systems. 2 Supramolecular gels based on low molecular weight gelators (LMWGs) 3–10 are a fascinating class of soft materials because the bulk properties of these materials depend on the nanoscale self-assembly of the gelators, which can be tuned by manipulating the self-assembly process. 11–16 Multi-component systems based on LMWGs possess properties beyond their single-component counterparts.…”
Section: Introductionmentioning
confidence: 99%